2009 IEEE International Symposium on Industrial Electronics 2009
DOI: 10.1109/isie.2009.5222732
|View full text |Cite
|
Sign up to set email alerts
|

A cogging torque compensating disturbance estimator for DC motor speed regulation: Design and experimentation

Abstract: A disturbance estimator was designed and integrated into an existing proportional and integral controller DC motor speed control system to improve the speed regulation. The DC motor in the existing control system possessed a large amount of cogging torque, causing a periodic speed error. This cogging torque was treated as an equivalent input disturbance which then was estimated using a disturbance estimator. The estimated disturbance was utilized to reject the cogging torque. The speed response was largely imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Then, we show that the gain of the proposed state observer is independent of the feedback motor speed. Simulation and experimental results for an actual brushless DC motor verify the effectiveness of the proposed method more than the previous study of [10].…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…Then, we show that the gain of the proposed state observer is independent of the feedback motor speed. Simulation and experimental results for an actual brushless DC motor verify the effectiveness of the proposed method more than the previous study of [10].…”
Section: Introductionmentioning
confidence: 55%
“…Although the motor speed randomly oscillates around the reference trajectory due to the measurement noises, we can see effective tracking performance. Finally, we perform a simulation to compare the proposed observer with the conventional observer in [10] as depicted in Figure 6. While the motor speed tends to the reference trajectory all target speed 20, 40, and 10 rad/s, it is shown that with the conventional observer, the output speed effectively tracks the target speeds 20 and 10 rad/s, but not for 40 rad/s.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations